Discussion about the contribution of water to the shale gas reserves within high-over matured shale rocks. Issue 1 (November 2020) - Li, S D; Xu, J B; Wei, Z W; Wang, H Z; Deng, Q; Cheng, B; Liao, Z W
Abstract: The shale gas currently exploited in China is mainly featured by high thermal maturity level and the methane concentration is generally more than 95% (v/v). The H/C atomic ratios of residual kerogen gradually decreased with the maturity whereas the source of elemental hydrogen contribution to the shale gas generation within high-over matured shale rocks is still vague. In recent years, some work indicated that the methane generation and its hydrogen isotope characteristics were greatly affected by elemental hydrogen from external water at the over-mature stage in shale rocks. The significance of water should be probed in the processes of geochemical degradation of residual kerogen and hydrocarbon generation in shales. It will be very meaningful to perform the hydrous pyrolysis experiments with heavy water to quantitatively appraise the impact of water on the hydrocarbon generation within shale rocks. A better understanding of the role that water plays on the shale gas generation and enrichment can be hopefully attained.